2006
DOI: 10.1002/ejic.200600306
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Structural, and Physical Studies of Basic CrIII and FeIII Benzilates and Benzoates: Evidence of Antisymmetric Exchange and Distributions of Isotropic and Antisymmetric Exchange Parameters

Abstract: The synthesis, crystal structures, spectroscopic and magnetic properties studies of four trinuclear oxo‐centered carboxylate complexes are reported and discussed: [Cr3(μ3‐O){O2C(OH)Ph2}6(H2O)3](NO3)·2H2O·3Me2CO (1·2H2O·3Me2CO), [Cr3(μ3‐O)(O2CPh)6(H2O)3](NO3)·1.9MeCN·0.5H2O (2·1.9MeCN·0.5H2O), [Fe3(μ3‐O){O2C(OH)Ph2}6(H2O)3](NO3)·5.69H2O (3·5.69H2O), and [Fe3(μ3‐O)(O2CPh)6(H2O)3](NO3)·3MeCN (4·3MeCN). From a crystallographic point of view, the three metal ions form an isosceles triangle in 1 and 3 (benzilato com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…It is well known that under the influence of antisymmetric exchange in trinuclear systems comprising half-integer spin ions, the ground S = 1/2 state is characterized by an axial g-tensor with g ⊥ < g iso (vide infra). 4,[47][48][49][50] Accordingly, here the low saturation value of the magnetization of 1 at 2.0 K is attributed to the anisotropy of the ground state, which is further corroborated by the EPR data. Finally, it should be mentioned that this model reproduces the low temperature isothermal magnetization data without the requirement of inter-cluster superexchange interactions.…”
Section: S S S S S S G S S S S S S H Ssupporting
confidence: 80%
See 1 more Smart Citation
“…It is well known that under the influence of antisymmetric exchange in trinuclear systems comprising half-integer spin ions, the ground S = 1/2 state is characterized by an axial g-tensor with g ⊥ < g iso (vide infra). 4,[47][48][49][50] Accordingly, here the low saturation value of the magnetization of 1 at 2.0 K is attributed to the anisotropy of the ground state, which is further corroborated by the EPR data. Finally, it should be mentioned that this model reproduces the low temperature isothermal magnetization data without the requirement of inter-cluster superexchange interactions.…”
Section: S S S S S S G S S S S S S H Ssupporting
confidence: 80%
“…2,3,8,[41][42][43][44][45] It has been demonstrated that the low-lying doublets of antiferromagnetically coupled half-integer spin triangles are non-degenerate, a property that is also referred to as "magnetic Jahn-Teller effect". 46 Usually, this non-degeneracy is rationalized by considering a decrease of the magnetic symmetry and/or the inclusion of an antisymmetric exchange term, characterized by a vector G. 4,[47][48][49][50][51] Whereas a dynamic mechanism has been recently proposed for the lifting of the degeneracy through isotropic interactions in highly symmetric triangles without a lowering of their symmetry, 52 static distortions provide a valid model for less symmetric triangles such as 1. Symmetry-lowering of the isotropic interactions was unsuccessful in fitting the experimental data ( Fig.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…meaning. An empirical analysis of the broadening of the g ⊥eff component was first presented by Sanakis et al 28 and subsequently applied in several other cases [29][30][31][32][33][34][35] where significant antisymmetric exchange was present. In those studies, such signals were analysed through the consideration of a series of fictitious axial S = 1/2 systems, of identical g || and distributed g ⊥ values.…”
Section: Empirical Determination Of the G ⊥ Distributionmentioning
confidence: 99%
“…For the chro- mium acetate, the CrÀm 3 -O distance is in the range of 1.88 to 1.94 and the CrÀCr distance is between 3.28 and 3.36 . [57][58][59][60][61] The differences are a result of the different axial ligands. For example, the replacement of water by a stronger donor like pyridine in the axial site leads to a lenghtening of the trans CrÀm 3 -O bonds.…”
Section: Trinuclear Chromium(iii) Formatementioning
confidence: 99%
“…Since the ratio j J 1 J À1 0 j is much smaller than one, results from EPR spectroscopy and INS can be fitted to equilateral as well as isosceles models. [61] The splittings of the spin states from the exchange couplings can be summarized as follows: The main exchange parameter J 0 creates five distinguishable states of different total spin S T = S 1 + S 2 + S 3 , …, 1/2, forming a fully discernible spin ladder. The coupling constant J 0 can be easily calculated from energy differences using Equation (3).…”
Section: Trinuclear Chromium(iii) Formatementioning
confidence: 99%